Collaborative Learning Strategy in Alfiyah Memorization and Arabic Language Learning at Madrasah Aliyah Mambaus Sholihin Gresik - Makinuddin, Mohammad; Farih, Muhammad; Ghofur, Abdul; Khofiyah, Ummu (UAS PRESS, 2026)
This study aims to analyse the application of collaborative learning strategies in strengthening the memorization of Alfiyah and its implications for Arabic language learning at Madrasah Aliyah Mambaus Sholihin Gresik. The method used is qualitative case study with data collection through interviews, observation, and documentation involving teachers and students as informants. The results show that collaborative learning is effective in increasing motivation, active participation, and mastery of memorizing Alfiyah, which has a positive impact on Arabic communication skills. Obstacles such as differences in ability and time limitations can be overcome by the teacher's role as a facilitator who provides group management and continuous motivation. The implications of this study encourage the systematic integration of collaborative strategies in madrasah Arabic curriculum as well as developing the use of technology in advanced learning.